Diagrammatic Representation and Inference 8th International Conference, Diagrams 2014, Melbourne, VIC, Australia, July 28 - August 1, 2014, Proceedings - Dwyer, Tim; Purchase, Helen; Delaney, Aidan (Lecture Notes in Artificial Intelligence,, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on the Theory and Application of Diagrams, Diagrams 2014, held in Melbourne, VIC, Australia in July/August 2014. The 15 revised full papers and 9 short papers presented together with 6 posters were carefully reviewed and selected from 40 submissions. The papers have been organized in the following topical sections: diagram layout, diagram notations, diagramming tools, diagrams in education, empirical studies and logic and diagrams.